Analisis Studi Kelayakan Bisnis Guest House Family Di Bandar Lampung - Sapmaya Wulan; Andala Rama Putra; Yosepha Windi Arini (Universitas Bandar Lampung (UBL), 2012)
The rapid development of the tourism sector and the business sector in Bandar Lampung, have an impact on the increasing demand for good accommodation for the middle class and the upper middle class. This is demonstrated by the level of habitable accommodation in Bandar Lampung that continues to increase every year. There are different types of accommodation including Guest House. Number of Guest House in Bandar Lampung is still very small, it is an opportunity for entrepreneurs to mendirian Family Guest House in Bandar Lampung. To set up a Guest House there should be a draft cost estimates are required, capital required and the benefits to be obtained. Before the House plan should first be carried out prior analysis Feasibility Study to determine the feasibility of the business. Therefore, the problem of this study is: Does the plan establish Family Guest House in Bandar Lampung is feasible? The purpose of this study was to determine the feasibility of establishing a plan Family House in Bandar Lampung. This study uses quantitative and qualitative methods. For the quantitative method used three criteria, namely Investment: Net Present Value (NPV), Net Benefit Cost Ratio (Net B / C), Internal Rate of Return (IRR); Analysis of Pay Back Period (PBP), and Analisisi Break Event Point (BEP) and qualitative methods are used for non-financial approach the technical aspects, market aspects and aspects of marketing, organizational and legal aspects, management aspects and economical aspects. Based on the analysis of financial NPV = 83.444.542,44; Net B / C = 1,633; IRR = 20,620%, Payback Period analysis for 8 years 2 months 23 days, analysis Break Event Point for 8 years 25 days. Based on the analysis of qualitative kuantitarif and it can be concluded that the plan of establishing Guest House Family feasible.